Oesophageal cavernous haemangioma - IMENPOUR, H.; MUTI, M.; PASTORINO, G. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
Esophageal cavernous haemangioma is an uncommon benign neoplasm. These tumors are usually discovered incidentally as they are often asymptomatic. The symptoms, if present, are bleeding and dysphagia. Endoscopic and radiographic features are nonspecific and histopathologic examination is required for definitive diagnosis and appropriate treatment. We herein report a case of a 69-year old man who presented with complain of mild dysphagia for solid foods. Endoscopic evaluation with transesophageal ultrasonography and CT revealed a 5 cm intramural tumor in the posterior wall of the upper esophagus. The tumor was resected and histological examination showed an esophageal cavernous haemangioma.